Evaluation of the effect of coronary artery bypass grafting on the right ventricular function using speckle tracking echocardiography - Abdelmoneum, Mahmoud Shawky; Elmeligy, Neama Ali; Eldarky, Elsayed Abdelkhalek; Mohamad, Mohamad Mahmoud (Journal of Cardiology and Cardiovascular Medicine, 2019)
Purpose: This was a prospective study conducted at Benha University hospital and National Heart Institute on one hundred patients undwent coronary artery bypass grafting (CABG) to evaluate the effect of CABG on the right ventricular (RV) function using speckle tracking echocardiography (STE). Methods: All cases were subjected to detailed medical history, full physical examination, 12 leads electrocardiogram (ECG), routine laboratory tests including (complete blood picture, liver functions, renal functions and lipid profile) and echocardiography either conventional echocardiography or STE, all parameters obtained before and within 2 weeks after surgery. Results: By conventional echocardiography there was statistically significant decrease in peak right ventricle systolic velociy (RVS) from (12.76 ± 1.72) to (7.33 ± 1.71) and tricuspid annular plane systolic excursion (TAPSE) from (22.8 ± 3.99) to (13.77 ± 4.63) among the studied patients after CABG. While there was significant increase in right ventricle fractional area change (RVFAC) from (44.69 ± 3.25) to (49.01 ± 3.36). On the other hand, there was non-significant change in right ventricle end diastolic diameter (RVEDD) at mid-cavity from (26.37 ± 2.72) to (26.53 ± 2.72) and basal segment from (36.05 ± 2.98) to (36.29 ± 3.04), right ventricle stroke volume (RVSV) from (65.44 ± 7.02) to (65.85 ± 6.86) and right myocardial performance index (RMPI) from (0.491 ± 0.088) to (0.498 ± 0.086). By STE There was statistically significant decrease in right ventricle global longitudinal strain (RVGLS) from (-20.63 to -14.1) after CABG. There was statistically significant decrease in right ventricle free wall longitudinal strain [apical decreased from (-23.73 to -13.7), mid-cavity decreased from (-25.76 to -11.53), basal decreased from (-20.39 to -10.13) and lateral wall declined from (-23.01 to -9.13)]. There was statistically significant decrease in interventricular septum longitudinal strain [apical decreased from (-19.77 to -10.06), mid-cavity decreased from (-17.81 to -10.87) and basal decreased from (-15.89 to -11.13)]. There was statistically significant increase in RV circumferential strain of lateral free wall from (-12.04 to -16.21), while there was non-significant change in RV circumferential strain of septum from (-19.77 ± 4.86) to (-20.37 ± 5.14). Conclusion: Distorted RV geometry after CABG can lead to altered deformation parameters, in other words longitudinal functional parameters may underestimate RV function and the decrease in RVGLS was compensated by increase in circumferential strain of lateral free wall of RV without change in RVSV or RMPI. Therefor changes in deformation parameters should always be interpreted in relation to change in geometry.Coronary artery bypass grafting